A new species of genus Urophonius Pocock, 1893 (Scorpiones, Bothriuridae), from Andean Mauline Chilean forests, with a phylogenetic re-analysis of the genus - Ojanguren Affilastro, Andres Alejandro (2024)
Urophonius trewanke sp. nov. is described from the Mauline Andean woods of northern Chilean Patagonia. This species belongs to the granulatus species group, which includes the most basal species within the genus. This species is only active in summer as in all species of its group. We performed a phylogenetic analysis of the genus Urophonius based on morphological characters to establish the position and relationships of the new species in the genus.